NARASI ILUSTRASI KONTEMPORER : SEBUAH PENDEKATAN EKSPERIMEN - Eston Kamelang Mauleti (Jurnal Nawala Visual, 2023)
In accordance with one of the elements of the Tri Dharma of Higher Education, Community Service was carried out through Contemporary Illustration Art Education training at PKBM Negeri 26 Bintaro, South Jakarta. The purpose of this training is to provide knowledge and briefing to students about the development of the world of illustration which is currently growing rapidly, especially in Indonesia. The basis of illustration is drawing, in this training students are given teaching and guidance on drawing illustrations through a contemporary illustration approach. The meaning of the word contemporary means "modern" or "current", then translated by a spontaneous experiment through character drawings and narration. Students experiment without being burdened with guilt (proportion or not) to produce narrated contemporary illustrations. The use of marker/felt tip pen materials supports the spontaneity and courage of students in drawing illustrations because the resulting lines are not easily erased and are as they are, like a child who draws spontaneously and happily